From research question to dissemination: how to design, analyse and present study results. Issue 3 (September 2018) - Fasola, Salvatore; Cilluffo, Giovanna; Nenna, Raffaella; La Grutta, Stefania
Today, the term "study" is very frequently used in quite a broad sense: survey, clinical trial, analysis, research and other terms with deeply different meanings are often generally indicated as "studies". A "study" can be generally defined as a process composed of several actions aimed to verify one or more hypotheses (objectives), with the ultimate goal of sharing the answers (results) with a target audience, in the form of a scientific paper, presentation or poster. The key for the success of a study lies in the careful design of all its different phases, from the statement of the objectives to the dissemination of the results http://ow.ly/5NbG30kHEnQ